Acquisition of Case System in Romani Language - Христо Кючуков (Психолінгвістика, 2019)
Introduction. The paper presents observations of the author on acquisition of case markers in the Romani language of two Roma children from Bulgaria. This is the first study ever done on acquisition of case system of Romani by children in their natural environment. The study is done in one of the biggest Roma settlement of Bulgaria in the city of Sofia. Romani being a new-Indian language has some features from the Indian languages but also adapted some features from some European languages. It has the ability to express one and the same idea either with a preposition or with a case marker.